Human UC-MSC-derived exosomes facilitate ovarian renovation in rats with chemotherapy-induced premature ovarian insufficiency - Pu, Xiaodi; Zhang, Leisheng; Zhang, Peiyu; Xu, Yaqiong; Wang, Jun; Zhao, Xiaomei; Dai, Zhihua; Zhou, Hua; Zhao, Shuyun; Fan, Anran (Frontiers in Endocrinology, 2023)
Premature ovarian insufficiency (POI) induced by chemotherapy is an intractable disorder with considerable incidence that commonly results in insufficient fertility and concomitant complications in female patients. Due to limitations in the current progress in POI diagnosis and treatment, there is an urgent need to develop novel remedies to improve ovarian function and protect fertility. The ameliorative effect of human umbilical cord mesenchymal stem cells (hUCMSCs) and exosomes derived from them in POI treatment could be a new hope for patients. Herein, we enriched and identified exosomes from hUCMSCs (hUCMSC-Exos). Then, systematic infusion of hUCMSC-Exos was accomplished via tail intravenous injection to investigate the feasibility of the treatment of rats with chemotherapy-induced POI by intraperitoneal injection of cyclophosphamide and busulfan. Ovarian functions in the indicated group were evaluated, including oestrous cycle, serum sex hormone levels, follicle counts, ovarian pathological changes, proliferation and apoptosis of granulosa cells, and reproductive ability testing. Furthermore, the potential influence of hUCMSC-Exos on ovarian tissues was illuminated by conducting RNA-seq and multifaceted bioinformatics analyses. POI rats with hUCMSC-Exo transplantation exhibited a decrease in follicle-stimulating hormone (FSH) and apoptosis of granulosa cells but an increase in oestradiol (E2), anti-Müllerian hormone (AMH), and the number of ovarian follicles and foetuses in the uterus. And the immunomodulation- and cellular vitality-associated gene sets in rats had also undergone moderate changes. Our data indicated the feasibility of hUCMSC-Exos in improving ovarian function and protecting fertility in the chemotherapy-induced POI rat. HUCMSC-Exos can improve the local microenvironment of ovarian tissue in POI rats by participating in immune regulation, cell viability, inflammation regulation, fibrosis and metabolism, and other related signal pathways.